(untitled) (Trabalho & Educação, 2018)
This paper considers the following question — where do computers, laptops and mobile phones come from and who produced them? Specific cases of digital labour are examined — the extraction of minerals in African mines under slave-like conditions; ICT manufacturing and assemblage in China (Foxconn); software engineering in India; call centre service work; software engineering at Google within Silicon Valley; and the digital labour of internet prosumers/users. Empirical data and empirical studies concerning these cases are systematically analysed and theoretically interpreted. The theoretical interpretations are grounded in Marxist political economy. The term ‘global value chain’ is criticised in favour of a complex and multidimensional understanding of Marx’s ‘mode of production’ for the purposes of conceptualizing digital labour. This kind of labour is transnational and involves various modes of production, relations of production and organisational forms (in the context of the productive forces). There is a complex global division of digital labour that connects and articulates various forms of productive forces, exploitation, modes of production, and variations within the dominant capitalist mode of production. ___ Este artigo levanta a seguinte questão: de onde vêm computadores, laptops e telefones móveis e quem os produz? Casos específicos de trabalho digital são examinados: extração de minerais na África sob condições análogas à escravidão; fabricação e montagem das tecnologias de informação e comunicação na China (Foxconn); engenharia de software na Índia; trabalho de serviços em call centers; engenharia de software na empresa Google no Vale do Silício; e o trabalho digital de internautas (prosumers da internet). Dados e estudos empíricos referentes a esses casos são sistematicamente analisados e teoricamente interpretados. As interpretações teóricas estão fundamentadas na economia política marxista. O termo ‘cadeia global de valor’ é criticado em favor de uma compreensão complexa e multidimensional da noção marxiana de ‘modo de produção’, com o propósito de conceituar o trabalho digital. Esse tipo de trabalho é transnacional e envolve vários modos de produção, relações de produção e formas organizacionais (no contexto das forças produtivas). Existe uma complexa divisão do trabalho digital que conecta e articula várias formas de forças produtivas, exploração, modos de produção e variações dentro do modo de produção capitalista dominante.